A hematite-based photoelectrochemical platform for visible light-induced biosensing1. Issue 22 (14th June 2015) - Ryu, Gyeong Min; Lee, Minah; Choi, Da Som; Park, Chan Beum
<x xml:space="preserve">Abstract</x> The first hematite-based PEC biosensor platform is developed and applied for the detection of NADH under visible-light irradiation.